2006
DOI: 10.1111/j.1945-1474.2006.tb00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety In Emergency Situations: A Web-Based Pediatric Arrest Medication Calculator

Abstract: To prevent adverse drug events for pediatric patients, increase care provider efficiency, and reduce stress for care providers, a technology tool was developed that calculates medication dosage requirements during emergency situations. This article describes a simple low-cost technological solution for improving patient safety and care-provider assurance. Follow-up studies provide validation of the technology tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…While portable, electronic, formula-based calculators have been used in medicine for over 15 years, there have been few studies evaluating the time savings associated with their use [1,2,6]. Several studies have shown that calculators are more accurate than traditional calculations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While portable, electronic, formula-based calculators have been used in medicine for over 15 years, there have been few studies evaluating the time savings associated with their use [1,2,6]. Several studies have shown that calculators are more accurate than traditional calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Medical calculators are common and are used to perform complex equations more efficiently and accurately [1][2][3][4]. These calculators are typically used by health care providers to determine values for specific formulas and require the user to input laboratory and/or demographic-based variables.…”
Section: Introductionmentioning
confidence: 99%
“…Context, Purpose, and Functions Automated calculation (of drug doses, dates, etc) eliminates manual computation errors, especially in high-stress situations 40 such as cardiopulmonary resuscitation of a child. For cases in which parameters (such as weight and height) are known, precalculated charts may provide an alternative.…”
Section: Cds: Clinical Calculatorsmentioning
confidence: 99%